International Production Networks and Economic Growth : The Case of the Western Balkan Countries - Shimbov, Bojan (Taylor and Francis, 2016)
The globalization of the world economy has given rise to new trade patterns through the intensification of international production networks (IPNs). This phenomenon has enabled countries to undertake more in-depth specialization in niche parts of the production chain, with important benefits for their economic activity and growth. The Western Balkan countries are no exception. With their recent integration into global markets, an increasingly large share of their trade flows entail intermediate goods that are eventually processed and exported. This article analyzes the impact of different degrees of participation in IPNs on the economic performance of the Western Balkan countries, thereby testing the hypothesis that trade created by international fragmentation of production may generate effects on economic growth beyond the beneficial influence of total or final goods trade. The article focuses on the period 2002–2013. The results, using a set of panel data models, show that the degree of involvement in IPNs significantly affects economic performance, which partly explains the observed differences in the growth rates of the Western Balkan countries. We also find that the positive influence of processing trade on economic growth is greater than the traditional gains of an increase in foreign demand.